LOCAL WISDOM SAGO PLANTATIONS' ASSISTANCE IN SUSTAINABLE SAGO FARMING: INNOVATION CLUSTERS AS A SUSTAINABLE SAGO DEVELOPMENT MODEL (2000-2023) - Lili Dahliani (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2023)
Global climate change poses a threat to food supplies since it leads to long-term droughts, excessive rains, pest infestations, and disease outbreaks. Indonesia has access to Sago, a promising food resource for ensuring food security. Sago thrives in wetlands and peatlands despite its considerable starch content. Therefore, effective sago plantation management requires addressing environmental, economic, social, and institutional considerations, as well as making significant advancements in sago innovation clusters. The presence of alternatives, such as the Sago innovation cluster, enhances collaboration and competitiveness. This study examines the growth of sago plantations and the indigenous knowledge systems used to maintain them. A qualitative systematic literature review (SLR) employing the TERASI technique scrutinizes pertinent journal articles published between 2000 and 2023. Harzing Publish, or Perish, utilizes Google Scholar as its primary source for academic literature. Retrieve scholarly material pertaining to the topics of "Sago Plantations," "Sustainability," "Local Wisdom," "Benefits of Sago Plantations," and "Innovation Clusters." Studies indicate that low productivity, insufficient farmer institutions, and unsupportive legislation hinder the growth of sago plantations. The utilization of indigenous knowledge in sago management enhances the long-term viability of gardens. Further investigation into the sago plantation is required. Subsequent research endeavors should prioritize the exploration of indigenous knowledge in order to establish enduring sago crops. For the sustainable growth of Sago, it is necessary to introduce innovative approaches, such as establishing Sago innovation clusters that are based on local knowledge, in order to gain a deeper understanding of the local communities.